2014
DOI: 10.1371/journal.pone.0090459
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Primary and Synchronous Metastatic Colorectal Cancers

Abstract: Approximately 50% of patients with primary colorectal carcinoma develop liver metastases. Understanding the genetic differences between primary colon cancer and their metastases to the liver is essential for devising a better therapeutic approach for this disease. We performed whole exome sequencing and copy number analysis for 15 triplets, each comprising normal colorectal tissue, primary colorectal carcinoma, and its synchronous matched liver metastasis. We analyzed the similarities and differences between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
87
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 50 publications
6
87
1
5
Order By: Relevance
“…Interestingly, our study also reports high occurrence of p.Q472H (21 out of 22 patients) type of mutation which highlights the role of p.Q472H mutation in the KDR gene. This is also substantiated by the study in which p.Q472H has been found to be mutated in large intestine carcinomas [12].…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, our study also reports high occurrence of p.Q472H (21 out of 22 patients) type of mutation which highlights the role of p.Q472H mutation in the KDR gene. This is also substantiated by the study in which p.Q472H has been found to be mutated in large intestine carcinomas [12].…”
Section: Discussionmentioning
confidence: 61%
“…45-48 Together, these findings indicate major differences between liver metastases and primary CRC as well as peritoneal metastases, including differences in immune cell infiltration and inhibitory molecule expression, which may be at least partly induced by the liver environment. We therefore suggest that TIL of MMR-proficient LM-CRC may be more sensitive to PD-1/PD-L1 blockade and other checkpoint inhibitors than TIL of MMR-proficient primary CRC and CRC metastases at other anatomical locations.…”
Section: Discussionmentioning
confidence: 83%
“…Screening, surgery, and medical therapies are successful in the management of early-stage colorectal REVIEW cancer, but far less effi cacious in advanced stages of the disease. A key reason for the limited success of colorectal cancerdirected therapies is the cancer's intrinsic heterogeneity, which is more prominent in the metastatic setting ( 5,6 ). Molecular characterization of colorectal cancers revealed that heterogeneity plays an important role, especially in the context of resistance to therapy.…”
Section: The Heterogeneous Molecular Landscape Of Colorectal Cancermentioning
confidence: 99%